Comparison of the maximum potential method with other methods for estimating the shape parameter of the general Rayleigh distribution using simulation - Ismail Hadi Chlope; Layla Matar Nasser (Iraqi Journal for Administrative Sciences, 2025)
The general Rayleigh distribution with two parameters is one of the important distributions at the level of research studies and has wide applications in the field of reliability and analysis of survival functions. In this research, the shape parameter of the general Rayleigh distribution was estimated through the least squares method with the PCT method. The two researchers proposed two methods: The first is to make a modification to the PCT method and the other is the Bayesian method by adopting a natural conjugate function, which is the exponential distribution, and adopting a quadratic loss function. The sample sizes were chosen (100, 50, 30, 20, 10), as the results showed that at values of 0.3 = small, the The sum of the squares of the error is less than the largest magnitude of the parameter value